Green Futures Navigating the Path to Environmental Resilience - Jaswal, Anshuman; Mukherjee, Debjani; Gunasekaran, Angappa; Kandpal, Vinay (Approaches to Global Sustainability, Markets, and Governance, 2025)
XIV, 553 p. 75 illus., 70 illus. in color.